Serious Games in der Logistik: Das Beispiel Routenplanung - Thomas Neukirchen; Markus Kleffmann; Wilhelm Koop; Arne Gels; Stefanie Jäger; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2018)
– This research paper addresses the long-standing question of how to train logistics employees in complex tasks like method-based routing. In former times, an in-depth formal qualification - usually academic - has been applied in order to qualify employees for this field of decision management in logistics operations. But increasingly as also presented here, smaller training-on-the-job and gamification approaches are taking hold. In order to highlight this, the paper is outlining the concept and gamification approach within the research and development project "MARTINA", directed at providing a commonplace available smartphone app for training such logistics tasks as routing. A reflection and evaluation of the applied methods as well as encountered technical restrictions is included to allow for future transfer of these results into other areas of training and logistics.
Keywords: 650